Fund Financial Support and Moral Hazard : Analytics and Empirics. (Policy Papers; Policy Paper ;, 2007)
Since Fund financial support helps reduce the expected cost of crises, members and markets might engage in greater risk-taking; in other words, moral hazard. Empirically, however, the Fund's rate of charge has adequately reflected the default risk it faces and the high political, social, and economic costs of crises are likely to limit debtor moral hazard. As regards the design of a contingent, crisis prevention instrument, the use of qualification standards can help address issues of debtor moral hazard directly. In addition, the small amounts of Fund financial support -- in relation to a country's financial needs -- suggest that creditor moral hazard is likely to be limited. While existing empirical tests are far from definitive, the paper suggests that creditor moral hazard is less likely to be a concern after the Fund sent the signal in mid-1998 that it would interrupt support when program success is unlikely.